2006
DOI: 10.4049/jimmunol.177.9.6422
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine Induces Mast Cell Adhesion and Migration

Abstract: The neurotransmitter serotonin (5-hydroxytryptamine (5-HT)) is implicated in enhancing inflammatory reactions of skin, lung, and gastrointestinal tract. To determine whether 5-HT acts, in part, through mast cells (MC), we first established that mouse bone marrow-derived MC (mBMMC) and human CD34+-derived MC (huMC) expressed mRNA for multiple 5-HT receptors. We next determined the effect of 5-HT on mouse and human MC degranulation, adhesion, and chemotaxis. We found no evidence that 5-HT degranulates MC or modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 52 publications
1
109
0
3
Order By: Relevance
“…Serotonin receptors belong to the G-protein-coupled receptor family with exception of the 5-HT 3 receptor, which is an ion channel (Barnes and Sharp, 1999). Despite the major role of 5-HT in the CNS, ∼90% of 5-HT is produced in the gastro-intestinal tract (Racké et al, 1996), where it is involved in the regulation of multiple physiological processes such as stimulation of cytokine and chemokine production (Dürk et al, 2005;Idzko et al, 2004;Müller et al, 2009), cell proliferation (Pakala and Benedict, 1998;Pakala et al, 1997), migration (Kushnir-Sukhov et al, 2006;Müller et al, 2009;Tamura et al, 1997) and the regulation of the immune system (Ahern, 2011). Expression of 5-HT receptors has been identified on a broad range of immune cells, including T cells (O'Connell et al, 2006), macrophages (Mikulski et al, 2010) and dendritic cells (Idzko et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin receptors belong to the G-protein-coupled receptor family with exception of the 5-HT 3 receptor, which is an ion channel (Barnes and Sharp, 1999). Despite the major role of 5-HT in the CNS, ∼90% of 5-HT is produced in the gastro-intestinal tract (Racké et al, 1996), where it is involved in the regulation of multiple physiological processes such as stimulation of cytokine and chemokine production (Dürk et al, 2005;Idzko et al, 2004;Müller et al, 2009), cell proliferation (Pakala and Benedict, 1998;Pakala et al, 1997), migration (Kushnir-Sukhov et al, 2006;Müller et al, 2009;Tamura et al, 1997) and the regulation of the immune system (Ahern, 2011). Expression of 5-HT receptors has been identified on a broad range of immune cells, including T cells (O'Connell et al, 2006), macrophages (Mikulski et al, 2010) and dendritic cells (Idzko et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, stem cell factor, CCL2, and TGFbeta1 are also chemotactic for mast cells (Nilsson et al, 1994;Berger et al, 2003;Collington et al, 2010). It has been demonstrated that 5-Hydroxytryptamine can induce mast cell adhesion and migration as well (Kushnir-Sukhov et al, 2006). Therefore, further work is required to identify some other important factors that may be involved in mast cells migration.…”
Section: Discussionmentioning
confidence: 99%
“…CNG channels are functionally expressed in alveolar epithelial type II cells and may contribute to the fluid-reabsorptive driving force in the adult lung (Kemp et al, 2001). Of the mast-cell amines, the neurotransmitter 5-HT has a potential role in the pathophysiology of fibrosis (Aldenborg et al, 1993) and is implicated in enhancement of the inflammatory reactions of various organs including the lung (Kushnir-Sukhov et al, 2006). Recently, calcium ionhomeostasis was reported as having a physiological role for 5-HT and serotoninergic receptors in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%